La revanche du territoire - Daniel Latouche; Guillaume Côté (Netcom)
This article shows that in France, Information society related policies are featuring many orientations and leadership changes. At first, they aimed to fill a technology gap. Afterwards, social objectives were put at first and then, policies were pursuing territorial development goals. Lately, French policies were mostly related to e-government implementation. By a neo-institutional approach, we will show that this new policy field represents an opportunity to create structures which do not establish a stable road map. Hence, this article is underlying how and for what reasons local authorities enactment of the Information society occurred and putting in emphasis little evaluation effort of the policies. Consequently, the “society” and its “informatization” came second on the priority lists.